Hannibal Hamlin papers - Hamlin, Hannibal, 1809-1891.
ALsS written by Hamlin to Ferguson Haines, W. P. Haines, Melvin Lord, and others and a check (1854) drawn on Corcoran & Riggs bank; and a manuscript record book (1837-1842) of notary public Charles J. Hardy, Natchitoches Parish, La., listing sales of slaves and land and other legal matters and a blank Confederate military form, both of which were collected by Hamlin during the Civil War.
Vice president of the United States, governor of Maine, and U.S. representative and senator from Maine.
Collection material in English.
Keywords: Haines, Ferguson -- Correspondence; Haines, W. P. -- Correspondence; Hardy, Charles J; Lord, Melvin, -- 1791-1876 -- Correspondence; Confederate States of America. -- Army; Corcoran & Riggs; Land tenure -- Louisiana -- Natchitoches Parish; Slave trade -- Louisiana -- Natchitoches Parish; United States -- History -- Civil War, 1861-1865.; Governors -- Maine; Representatives, U.S. Congress -- Maine; Senators, U.S. Congress -- Maine; Vice-Presidents -- United States